A Comparative Analysis of Fatigue Resistance in Asphalt Wearing Courses Modified with 7% Content of Natural Rubber and Waste Tire Rubber - Hendrik Jimmyanto; Ramadhani Ramadhani; Rindu Twidi Bethary; Lega Lubis Reskita; Kiagus Muhammad Aminuddin (Jurnal Fondasi, 2026)
Fatigue cracking remains a primary structural failure in flexible pavements, necessitating the development of more ductile and resilient asphalt mixtures. This study investigates the fatigue performance of Asphalt Concrete-Wearing Course (AC-WC) modified with 7% natural rubber and waste tire rubber, specifically comparing Pre-vulcanized Latex (LP7) and a combination of solid natural rubber and crumb rubber (KACR 7) against a conventional 60/70 penetration grade asphalt (Aspen). The experimental program employed the Indirect Tensile Fatigue Test (ITFT) under a controlled-stress mode of 500 kPa at 20°C to evaluate stiffness degradation, horizontal deformation, and cumulative strain. The results indicate that the 7% rubber modification induces a significant "softening effect," reducing the initial stiffness modulus from 30,136 MPa in the control sample to 19,055 MPa in the LP7 variant. This reduction in stiffness is accompanied by an increase in initial strain, with LP7 and KACR 7 reaching 214 μϵ and 164 μϵ, respectively, compared to only 94 μϵ for the Aspen sample. While the control sample demonstrated a longer laboratory fatigue life (Nf) of 3,381 cycles, the rubber-modified mixtures showed superior ductility and energy dissipation capacity through higher cumulative horizontal strain. Furthermore, evaluation against perpetual pavement criteria revealed that only the Aspen sample falls within the ideal endurance limit (